Contribution of Public Figures in Political Parties and the 2024 General Election - Ekalindo Jaroenchai; Fadhila Akbar Nurhakim; Mariska Jasiaat; Maimunah Rusydah Istiqomah; Ahmad Kamalul Albar; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2023)
Indonesia is a country that adheres to a presidential system of government and in Indonesia uses a democratic form of government. The thing that is very inherent in democracy is general elections. Leader candidates are proposals from political parties that have received a minimum percentage of votes. In an effort to get a sufficient percentage of the vote, many parties try to lure public figures to join the party in the hope of getting enough votes to be able to participate in the struggle for legislative seats. The purpose of this study is to address the public and provide information about public figures in the struggle for legislative seats and the relationship between public figures and political parties in general elections in Indonesia in 2024. The research method used in this journal article uses qualitative research methods. By using library research, many political parties are trying to entice public figures to join the party in the hope of getting enough votes to be able to participate in the struggle for legislative seats.